2018
DOI: 10.3390/nano8121070
|View full text |Cite
|
Sign up to set email alerts
|

Intramolecular Metal Exchange Reaction Promoted by Thiol Ligands

Abstract: The synthesis of an alloy nanocluster that is atomically precise is the key to understanding the metal synergy effect at the atomic level. Using the Ag2Au25(SR)18 nanocluster as a model, we reported a third approach for the metal exchange reaction, that is, intramolecular metal exchange. The surface adsorbed metal ions (i.e., Ag) can be exchanged with the kernel metal atoms (i.e., Au) that are promoted by thiol ligands. The exchanged gold atoms can be further stripped by the thiol ligands, and produce the AgxA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 25 publications
0
23
0
Order By: Relevance
“… 24 Metal migration in Ag 2 Au 25 clusters was found to occur also intramolecularly when exposed to a thiol solution. 25 Altogether, this demonstrated that in solution, the structure of doped nanoclusters is not static but evolves under different conditions.…”
Section: Introductionmentioning
confidence: 88%
“… 24 Metal migration in Ag 2 Au 25 clusters was found to occur also intramolecularly when exposed to a thiol solution. 25 Altogether, this demonstrated that in solution, the structure of doped nanoclusters is not static but evolves under different conditions.…”
Section: Introductionmentioning
confidence: 88%
“…Under particular reaction conditions, such metal exchange does not occur, and another type of metal atoms or metal ions are deposited on the surface of the metal NCs (deposition of metal atoms/ions; Figure 5F). 184,200,201 In these synthetic methods, the method shown in Figure 5A is superior for systematically isolating a series of metal NCs, and the method shown in Figure 5B−F is superior for size-selectively synthesizing a specific metal NC. In addition to these methods, there have been several…”
Section: Ligand-protected Atomically Precise Metal Ncsmentioning
confidence: 99%
“…The aim of this Special Issue on "Supramolecular Gold Chemistry" was to provide a unique international forum aimed at covering a broad description of results involving the supramolecular chemistry of gold with a special focus on the gold-sulfur interface leading to hybrid materials, ranging from gold-thiolate complexes, [3] to thiolate-protected gold nanoclusters [4][5][6][7][8][9][10][11] and gold-thiolate supramolecular assemblies or nanoparticles. [12][13][14] The role of thiolates on the structure and optical features of gold nanohybrid systems (ranging from plasmonic gold nanoparticles and fluorescent gold nanoclusters to self-assembled Au-containing thiolated coordination polymers) has been highlighted in the review article by Csapó and coworkers [14].…”
mentioning
confidence: 99%
“…Innovative strategies include a metal exchange reaction that leads to a new cluster compound in particular alloy nanoclusters. Zhu and coworkers describe a new type of metal exchange: self-alloying induced by intramolecular metal exchange, to produce the Ag x Au 25−x (SR) 18 − nanocluster [4]. Moreover, new synthetic routes, beyond wet chemistry using a reducing agent, are being explored.…”
mentioning
confidence: 99%